2014
DOI: 10.1134/s0031918x14130080
|View full text |Cite
|
Sign up to set email alerts
|

Creep performance of Zr-1Nb-0.75Sn-0.1Fe cladding tubes with optimized Sn content

Abstract: Creep properties of stress relieved Zr-1Nb-0.75Sn-0.1Fe alloy with a lower Sn content were studied. Zr-1Nb-0.75Sn-0.1Fe alloy was found to have stress exponents of 6-7, independent of stress level, unlike Zr-1Nb-1Sn-0.1Fe alloy, in which the transition of stress exponent with increase of stress was observed. The constancy of stress exponent, without the transition observed in Zr-1Nb-0.75Sn-0.1Fe alloy with lower Sn content, is associated with the decrease of Sn atoms. The activation energies for creep defor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In order to examine the creep characteristics in the circumferential direction, the Zr alloy rings with the width of 4 mm were cut vertically against the axial direction of tubes. In this study, a special grip with two halfcylinders with 1 mm wide space between them was used to strain the ring specimen with maintaining a circular configuration of the ring in contact with the grips all the way during the tests [1][2][3]5]. Constant stress creep testers were used to investigate the effect of grain size on creep deformation behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the creep characteristics in the circumferential direction, the Zr alloy rings with the width of 4 mm were cut vertically against the axial direction of tubes. In this study, a special grip with two halfcylinders with 1 mm wide space between them was used to strain the ring specimen with maintaining a circular configuration of the ring in contact with the grips all the way during the tests [1][2][3]5]. Constant stress creep testers were used to investigate the effect of grain size on creep deformation behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Zr alloy cladding tubes play important roles not only as the first barrier preventing nuclear fission products in the UO 2 pellet from being released into the reactor coolant, but also as the conductor transferring nuclear fission-induced heat effectively to the coolant. From the viewpoint of the nuclear fuel integrity and the reactor safety [1][2][3], high temperature creep behavior of Zr cladding tubes along with corrosion behavior is one of the key performance parameters to be evaluated since they need to sustain the load arising from the pellet-clad mechanical interaction as well as the load caused by the reactor coolant over pressure acting on the outer surface of the Zr cladding tubes in the corrosive environment [2] It was also found that the higher heat treatment temperature after the final pilgering step lowered the mechanical strength, but enhanced the corrosion and growth resistance [5]. Some cladding tubes are being heat treated in the stress relieved condition after cold pilgering to render the better mechanical strength and creep strength while other tubes are being heat treated in the recrystallized condition to render the better corrosion resistance and growth resistance at the expense of the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%